Why caregivers have no autonomy-based reason to respect advance directives in dementia care - Lauridsen, Sigurd (Bioethics, 2023)
Advance directives (ADs) have for some time been championed by ethicists and patient associations alike as a tool that people newly diagnosed with dementia, or prior to onset, may use to ensure that their future care and treatment are organized in accordance with their interests. The idea is that autonomous people, not yet neurologically affected by dementia, can design directives for their future care that caregivers are morally obligated to respect because they have been designed by autonomous individuals. In this paper, we first criticize the idea that ADs can retain moral authority in severe dementia by arguing that it is paradoxical. Second, we consider two arguments that initially seem to refute this critique of ADs, but we eventually dismiss them. The first argument states that ADs retain moral authority in severe dementia because autonomously formed interests, for example, ADs, can only be appropriately discarded by autonomous persons. This we term the historical autonomy argument. We dismiss it by demonstrating how we, in analog cases, are not obligated to continue to respect autonomously formed interests even though they have been discarded under nonappropriate conditions. The second argument is that ADs can be justified by what we term external interests. While we agree that people with severe dementia plausible can be said to have external interests, we show that ADs cannot express such interests and hence cannot be justified by them. We conclude that none of the discussed arguments support the use of ADs and because of this, the idea of ADs should be reassigned.